Applying potentials to conductive materials impairs High-loading anaerobic digestion performance by affecting direct interspecies electron transfer. (February 2020) - Liu, Xinying; Chen, Qian; Sun, Dezhi; Wang, Yumingzi; Dong, He; Dang, Yan; Holmes, Dawn E
Graphical abstract: Highlights: Application of current to carbon cloth impaired biomethanogenic reactor performance. Control reactors were stable at higher OLRs than reactors with applied current. Butyrate and propionate accumulated most rapidly in the positively poised reactor. Electrons were not efficiently channeled to methanogens when potential was applied. Abstract: In order to illustrate the impact that application of positive or negative potential to conductive materials can have on direct interspecies electron transfer (DIET) and reactor performance under high organic loading rates, three continuous laboratory-scale reactors with carbon-cloth electrodes poised at +0.7 V, −0.7 V (vs. Ag/AgCl) and no-potential were fed high concentrations of ethanol wastewater. While exoelectrogens and methanogens that are capable of DIET were significantly enriched in poised reactors, they performed worse than the non-current control. Volatile fatty acids (VFAs) accumulated more rapidly in the positively then negatively poised reactor, but neither could withstand high-loading rates. These results demonstrate that applying potential to conductive materials had a negative effect on anaerobic digestion under high-loading conditions.